2018
DOI: 10.1371/journal.pone.0192310
|View full text |Cite
|
Sign up to set email alerts
|

Prediction models for patients with esophageal or gastric cancer: A systematic review and meta-analysis

Abstract: BackgroundClinical prediction models are increasingly used to predict outcomes such as survival in cancer patients. The aim of this study was threefold. First, to perform a systematic review to identify available clinical prediction models for patients with esophageal and/or gastric cancer. Second, to evaluate sources of bias in the included studies. Third, to investigate the predictive performance of the prediction models using meta-analysis.MethodsMEDLINE, EMBASE, PsycINFO, CINAHL, and The Cochrane Library w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 79 publications
0
53
0
Order By: Relevance
“…When specific symptoms are present, such as diarrhea, these could be addressed immediately. Predictive QoL parameters may be added to prediction models for survival, 44,45 in addition to patient, tumor, and treatment characteristics, to improve their predictive outcome. Finally, QoL parameters may be considered as a stratification factor in clinical trials and should be included in the core set of mandatory baseline measurements.…”
Section: Discussionmentioning
confidence: 99%
“…When specific symptoms are present, such as diarrhea, these could be addressed immediately. Predictive QoL parameters may be added to prediction models for survival, 44,45 in addition to patient, tumor, and treatment characteristics, to improve their predictive outcome. Finally, QoL parameters may be considered as a stratification factor in clinical trials and should be included in the core set of mandatory baseline measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews of prediction models in oncology also concluded that external validation studies are lacking. Most prediction models provide a probability by using a score, nomogram or calculator (assistive), rather than recommending a treatment decision to the clinician (directive).…”
Section: Discussionmentioning
confidence: 99%
“…dose administration, timeline of use) are still needed [ 22 ]. Predicting patients’ prognoses via blood based biopsies, epigenetics, and autoantibodies still lack validity in locally advanced EC, requiring further investigation into potential progression biomarkers to improve patients’ treatment plans and outcomes [ 23 ].…”
Section: Introductionmentioning
confidence: 99%